Surfactant-assisted synthesis of Mo-V mixed oxide catalysts for upgraded one-step conversion of glycerol to acrylic acid - Rasteiro, Letícia F. [UNESP]; Vieira, Luiz H. [UNESP]; Santilli, Celso V. [UNESP]; Martins, Leandro [UNESP] (Royal Society of Chemistry (RSC), 2018)
The catalytic properties of Mo-V mixed oxides hydrothermally synthetized in the presence of ionic surfactants (SDS and CTAB) were investigated in the gas-phase oxidative dehydration of glycerol. The presence of surfactants promoted a change in morphology of MoV2O8 phase, directing to formation of rod-shaped crystals, and, consequently, an increase in macroporosity of materials, generated by intercrystallite spaces, when compared to a reference sample. Rod-like morphology stabilized the MoV2O8 mixed oxide phase during glycerol conversion, avoiding migration of vanadium from crystalline to amorphous phase, like observed in the reference sample, favoring the dynamic of reduction/reoxidation of vanadium and, consequently contributing to an increase in efficiency and stability of the catalyst. Both SDS and CTAB catalysts presented higher productivity of acrylic acid and good catalytic stability, with no coke formation and considerable decrease in COX evolution during 6 h of reaction. SDS presented the best catalytic results with 100% of conversion, 57% of acrylic acid selectivity and 36% of COX selectivity.